2013
DOI: 10.1111/jopy.12070
|View full text |Cite
|
Sign up to set email alerts
|

How Sacrifice Impacts the Giver and the Recipient: Insights From Approach‐Avoidance Motivational Theory

Abstract: This study investigated how sacrificing for approach versus avoidance goals shapes the giver's and the recipient's emotions and relationship quality. A sample of 80 dating couples participated in a three-part study in which they discussed sacrifice in the laboratory (Part 1), reported on their daily sacrifices for 14 days (Part 2), and completed a follow-up survey 3 months later (Part 3). When partners discussed a sacrifice they had made for approach goals, they experienced greater relationship quality, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…Several studies have shown that people experience positive intrapersonal (i.e., higher positive affect) and interpersonal (i.e., higher relationship satisfaction) outcomes when they sacrifice for approach motives, that is, when they focus on obtaining some anticipated reward. In contrast, people experience negative intrapersonal and interpersonal outcomes when they sacrifice for avoidance motives, that is, when they focus on negative outcomes that they want to avoid (Impett et al, ; Impett, Gere, Kogan, Gordon, & Keltner, ). These effects are largely accounted by differences in authenticity that people experience when they sacrifice for approach versus avoidance goals (Impett, Javam, Le, Asyabi‐Eshghi, & Kogan, ).…”
Section: Why Do People Sacrifice?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that people experience positive intrapersonal (i.e., higher positive affect) and interpersonal (i.e., higher relationship satisfaction) outcomes when they sacrifice for approach motives, that is, when they focus on obtaining some anticipated reward. In contrast, people experience negative intrapersonal and interpersonal outcomes when they sacrifice for avoidance motives, that is, when they focus on negative outcomes that they want to avoid (Impett et al, ; Impett, Gere, Kogan, Gordon, & Keltner, ). These effects are largely accounted by differences in authenticity that people experience when they sacrifice for approach versus avoidance goals (Impett, Javam, Le, Asyabi‐Eshghi, & Kogan, ).…”
Section: Why Do People Sacrifice?mentioning
confidence: 99%
“…The motives that people pursue when making a sacrifice also impact the partner who receives (or perceives their partner make) the sacrifice. When people perceive that their partner make a sacrifice for approach motives, they experience personal and relationship benefits, whereas when people perceive that their partner sacrifice for avoidance motives, they experience poorer personal well‐being and relationship quality (Impett et al, , ).…”
Section: Why Do People Sacrifice?mentioning
confidence: 99%
“…Secondly, some related theories were applied to the study of sacrifice to explain the paradox. For example, ‘approach‐avoidance theory’ was used to define sacrifice motivation, and consistent results showed that approach‐motivated sacrifices related to higher relationship satisfaction, whereas avoidance‐motivated sacrifice led to a decrease in relationship stability (Impett et al ., ; Impett, Gere, Kogan, Gordon and Keltner, ; Impett et al ., ; Impett, Javam, Le, Asyabi‐Eshghi and Kogan, ). Moreover, some personal factors were given more attention in order to explore the mechanism of sacrifice, such as attachment style and self‐control (Findley, Carvallo and Bartak, ; Impett and Gordon, ; Mattingly and Clark, ; Righetti, Finkenauer and Finkel, ; Ruppel and Curran, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research has mainly focused on examining cognitive and affective aspects related to relationship satisfaction (e.g., information processing, memory, experience of positive affect), and even though relationship research has demonstrated the importance of observational data (Gottman, 1994), to date only few studies on goal orientation in couples have included observational data (Impett, Gere, Kogan, Gordon, & Keltner, 2013;Impett et al, 2010). In most…”
Section: Strength Limitations and Future Directionsmentioning
confidence: 99%